2011
DOI: 10.1007/s10681-011-0438-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome constitution of Narcissus variety, ‘Tête-à-Tête’, analysed through GISH and NBS profiling

Abstract: The Narcissus variety, 'Tête-à-Tête', has been the most popular variety since 1949, and a well known allotriploid (2n = 3x = 24 ? B) of spontaneous origin. Because the identity of one of the parents of this variety was uncertain, the genome constitution of 'Tête-à-Tête' was investigated by using genomic in situ hybridization (GISH) and NBS profiling. Both of these techniques confirmed that two different species of Narcissus, viz., N. tazetta (2n = 2x = 20) and N. cyclamineus (2n = 2x = 14) are the parents. GIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Similarly in Lilium, GISH can distinguish parental genomes in F 1 , BC 1 and BC 2 when their parental species usually belong to different sections and their F 1 hybrids are highly sterile, then the two parental genomes are different or dissimilar; otherwise, GISH could not discriminate them and the parental genomes are similar or common (Zhou et al 2008;Barba-Gonzalez et al 2006;Lim et al 2003;Van Tuyl et al 2018). These are the reasons why Wu et al (2011) and the present research get same GISH results though the former use N. cyclamineus's DNA as probe while the latter use Dutch Master's DNA as probe. Brandham and Kirton (1987) point out that 'Tête-à-Tête' is from [(N. cyclamineus × N. tazatta 'Soleil d'Or')] × 'Op' (presumably diploid).…”
Section: Polyploidization Of Narcissussupporting
confidence: 74%
See 2 more Smart Citations
“…Similarly in Lilium, GISH can distinguish parental genomes in F 1 , BC 1 and BC 2 when their parental species usually belong to different sections and their F 1 hybrids are highly sterile, then the two parental genomes are different or dissimilar; otherwise, GISH could not discriminate them and the parental genomes are similar or common (Zhou et al 2008;Barba-Gonzalez et al 2006;Lim et al 2003;Van Tuyl et al 2018). These are the reasons why Wu et al (2011) and the present research get same GISH results though the former use N. cyclamineus's DNA as probe while the latter use Dutch Master's DNA as probe. Brandham and Kirton (1987) point out that 'Tête-à-Tête' is from [(N. cyclamineus × N. tazatta 'Soleil d'Or')] × 'Op' (presumably diploid).…”
Section: Polyploidization Of Narcissussupporting
confidence: 74%
“…3 and 4). A previous report indicates that 'Tête-à-Tête' contains one set of ten N. tazetta chromosomes and two sets of seven N. cyclamineus chromosomes plus a B -chromosome (Wu et al 2011); while the present GISH indicates that it has a genome of N. tazetta and two genomes of 'Dutch Master'. Seemingly, it contains one genome of N. tazette and two genomes of N. cyclamineus or 'Dutch Master'.…”
Section: Polyploidization Of Narcissusmentioning
confidence: 50%
See 1 more Smart Citation
“…Harlan and De Wet (1975) suggested that sexual polyploidization is the main mechanism in the origin and evolution of polyploids, so these facts corroborate that the evolution of the genus Agave may have occurred through 2n gametes, just as the existence of several degrees of ploidy. Although there are many known polyploid species so far, the reports about the presence of 2n pollen are much less; in the order Asparagales there are very few reports about the presence of 2n pollen, some examples are Asparagus and Narcissus (Camadro 1994; Wu et al 2011); this is the first report of its kind in the Agavaceae family in which the presence of 2n pollen, its frequencies, as well as the mechanism through which this type of gametes are formed in A. tequilana and A. angustifolia are reported.…”
Section: Discussionmentioning
confidence: 99%